2021
DOI: 10.3390/ijms221910787
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Targets of Nucleotide-Tagged Trithiolato-Bridged Arene Ruthenium Complexes in the Protozoan Parasites Toxoplasma gondii and Trypanosoma brucei

Abstract: Toxoplasma gondii is an apicomplexan parasite that infects and proliferates within many different types of host cells and infects virtually all warm-blooded animals and humans. Trypanosoma brucei is an extracellular kinetoplastid that causes human African trypanosomiasis and Nagana disease in cattle, primarily in rural sub-Saharan Africa. Current treatments against both parasites have limitations, e.g., suboptimal efficacy and adverse side effects. Here, we investigate the potential cellular and molecular targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
(57 reference statements)
1
21
0
Order By: Relevance
“…In this study, under the pos ion mode (72 h), the amount of the substance was upregulated and involved in metabolic pathways and purine metabolism, which showed that the substance was of great significance to the normal physiology of cells. It has been reported that Toxoplasma gondii cannot synthesize purine, and it is very dependent on the enzymes and intermediates in the purine salvage pathway [ 63 ]. The purines of infected cells are upregulated after being treated with drugs, so we speculate that T. annulata may not have the ability to synthesize purines, and thus they will be upregulated after parasite removal.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, under the pos ion mode (72 h), the amount of the substance was upregulated and involved in metabolic pathways and purine metabolism, which showed that the substance was of great significance to the normal physiology of cells. It has been reported that Toxoplasma gondii cannot synthesize purine, and it is very dependent on the enzymes and intermediates in the purine salvage pathway [ 63 ]. The purines of infected cells are upregulated after being treated with drugs, so we speculate that T. annulata may not have the ability to synthesize purines, and thus they will be upregulated after parasite removal.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the columns were separated, and the binding proteins were eluted with 50 mM acetic acid (5 mL per column). The eluates were lyophilized and stored at −80 • C [45].…”
Section: Protein Extraction and Affinity Chromatographymentioning
confidence: 99%
“…Moreover, the potential cellular and molecular targets of conjugate 14 were recently investigated 124 .…”
Section: Assessment Of the In Vitro Activity Against T Gondii β-Gal A...mentioning
confidence: 99%